1997
DOI: 10.1007/bf03160720
|View full text |Cite
|
Sign up to set email alerts
|

Measurement of wetland hydroperiod using harmonic analysis

Abstract: The pattern of water-level fluctuations in a wetland is its hydroperiod. Characterization of this pattern cannot be accomplished by measuring a single parameter, but some means of measuring hydroperiod is needed so that comparisons can be made both between wetlands and within a single wetland over time. Harmonic analysis can be used to characterize hydroperiod quantitatively by obtaining the amplitude and timing of the dominant periodic component in a time series of water levels. The utility of this method is … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
13
0

Year Published

1999
1999
2016
2016

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(14 citation statements)
references
References 8 publications
1
13
0
Order By: Relevance
“…While there is considerable evidence for how range in water depth affects plants (Leira and Cantonati, 2008) there are fewer studies that have addressed this for animals. In Everglades National Park, wood stork nest failure was more likely to occur in years with lower hydroperiod amplitude because of less effective concentration of prey fish (Nuttle, 1997). This was also support by more recent work showing nesting effort for wood storks, white ibises, and great egrets in years when amplitude was high and days of rising water levels were low (Botson and Gawlik, unpublished data).…”
Section: Discussionsupporting
confidence: 61%
See 1 more Smart Citation
“…While there is considerable evidence for how range in water depth affects plants (Leira and Cantonati, 2008) there are fewer studies that have addressed this for animals. In Everglades National Park, wood stork nest failure was more likely to occur in years with lower hydroperiod amplitude because of less effective concentration of prey fish (Nuttle, 1997). This was also support by more recent work showing nesting effort for wood storks, white ibises, and great egrets in years when amplitude was high and days of rising water levels were low (Botson and Gawlik, unpublished data).…”
Section: Discussionsupporting
confidence: 61%
“…Higher fluctuations should result in higher productivity and higher alligator body condition. Nuttle (1997) and Botson and Gawlik (In Review) found positive relationships between wading bird nesting success and harmonic amplitude.…”
Section: Rangementioning
confidence: 96%
“…In three successive growing seasons, variability in the controlling factor of precipitation and buffering of geomorphic position (connection to streamflow) resulted in distinct hydroperiods for the three studied fens. Our three years of growing season water table data, in addition to sporadic winter water level measurements (data not shown), were not extensive enough to compute significant hydroperiod statistics ( sensu Nuttle's (1997) harmonic mean approach). Nor were our data continuous enough to perform a proper analysis of crossing properties of the water table ( sensu Bras & Rodriguez‐Iturbe, 1994).…”
Section: Discussionmentioning
confidence: 99%
“…The challenge in assessing the hydroperiod for a particular site is to determine an appropriate statistic or set of statistics to characterize the temporal variability of the hydrograph. In addition to the usual parametric and non-parametric measures of location (mean, median) and scale (standard deviation, interquartile range), we attempted to use harmonic analysis as described elsewhere (e.g., Long and Nestler 1996;Nuttle 1997). However, the hydrographs did not show statistically significant periodic components over the single growing season, perhaps due to the erratic nature of the hydrographs over shorter time scales (i.e., hourly and dally scales compared to monthly and annual scales).…”
Section: Characterizing Hydrologymentioning
confidence: 99%